Biodiesel Production from Macro Algae as a Green Fuel for Diesel Engine - A. S., Ahmed; S., Khan; S., Hamdan; R., Rahman; A., Kalam; H.H., Masjuki; T.M.I., Mahlia (Universiti Tenaga Nasional, 2010)
Plant oils or triglycerides are converted through the transesterification reaction with methanol and base catalyst to produce fatty acid methyl esters (FAME) or Biodiesel. Production of biodiesel from plant oil is a renewable, sustainable and alternative of petroleum based fuel. Algae oil from macroalgae has the potential to become a sustainable fuel source as biodiesel. Macroalgae are produced through photosynthesis by utilizing sunlight, carbon dioxide, water and other nutrients. The lipid contents or oil in algae, once extracted and purified, represent an excellent sustainable feedstock for biodiesel production. Three different species of macroalgae (Spirogyra, Cladophora and Gracilaria) were used for algal oil extraction in this study. The algal oil was extracted by physical and chemical extraction method. The transesterification reaction of algal oil with methanol and base catalyst was used for the production of biodiesel. In engine performance test, the algal biodiesel blends showed slight increase in specific fuel consumption but biodiesel blends showed higher brake power. The emission of carbon monoxide (CO), hydrocarbon (HC) and nitrogen oxides (NOx) reduced as biodiesel blend percentage increased over engine speed range.